2005
DOI: 10.1182/blood.v106.11.783.783
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Therapy Alone and in Combination with Dexamethasone for Patients with Previously Untreated Multiple Myeloma.

Abstract: Introduction: Bortezomib ± dexamethasone (dex) has demonstrated impressive activity in the treatment of relapsed and refractory myeloma. Bortezomib is currently approved in the U.S. for multiple myeloma patients who have received at least 1 prior therapy. We are conducting a phase 2 trial evaluating bortezomib alone or in combination with dex as first-line therapy in patients with myeloma. Methods: Eligible patients had measurable disease and a Karnofsky performance score (KPS) ≥ 50%. Bortezomib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a second phase II trial, bortezomib 1.3 mg/m 2 in the usual regimen was administered alone or with 40 mg of oral dexamethasone if patients did not achieve at least a partial response after two cycles, or had less than a complete response after four cycles [25]. For the 23 patients who completed the study and were evaluable, bortezomib was found to be highly active in the first-line treatment of multiple myeloma, with an overall major response rate of 83% (CR, 13%; nCR, 17%; PR, 53%) and minor response rate of 13%.…”
Section: Efficacy Of Bortezomib In Previously Untreated Patientsmentioning
confidence: 99%
“…In a second phase II trial, bortezomib 1.3 mg/m 2 in the usual regimen was administered alone or with 40 mg of oral dexamethasone if patients did not achieve at least a partial response after two cycles, or had less than a complete response after four cycles [25]. For the 23 patients who completed the study and were evaluable, bortezomib was found to be highly active in the first-line treatment of multiple myeloma, with an overall major response rate of 83% (CR, 13%; nCR, 17%; PR, 53%) and minor response rate of 13%.…”
Section: Efficacy Of Bortezomib In Previously Untreated Patientsmentioning
confidence: 99%
“…The most common adverse events were neuropathy, fatigue, constipation, nausea, and neutropenia. Overall, adverse events were found to be predictable and manageable 2 …”
mentioning
confidence: 99%
“…The success of bortezomib in the treatment of relapsed and refractory MM provides the rationale for its use in the treatment of newly diagnosed disease, both as single agent and in combination with conventional chemotherapy and autologous stem cell transplantation. In a Phase II study in patients with previously untreated MM, an overall response rate (ORR) of 90%, with a complete response (CR) plus near CR (nCR) rate of 19%, was achieved in 48 evaluable patients receiving bortezomib plus dexamethasone 2 . Dexamethasone was added in patients with less than a partial response (PR) after two cycles or less than a CR after four cycles.…”
mentioning
confidence: 99%